Managing the Morbidity Associated with Respiratory Viral Infections in Children with Congenital Heart Disease - Joseph M. Geskey; Stephen E. Cyran (International Journal of Pediatrics)
Children with congenital heart disease (CHD) are at risk for increased morbidity from viral lower respiratory tract infections because of anatomical cardiac lesions than can worsen an already compromised respiratory status. Respiratory syncytial virus (RSV) remains an important pathogen in contributing toward the morbidity in this population. Although the acute treatment of RSV largely remains supportive, the development of monoclonal antibodies, such as palivuzumab, has reduced the RSV-related hospitalization rate in children with CHD. This review highlights the specific cardiac complications of RSV infection, the acute treatment of bronchiolitis in patients with CHD, and the search for new therapies against RSV, including an effective vaccine, because of the high cost associated with immunoprophylaxis and its lack of reducing RSV-related mortality.